Análisis de los Beneficios Sociales en la Empresa Bananera Anuk del Cantón Baba - Garcés Carpio, Mercedes Estefanía (2021)
This case study deals with the analysis of social benefits at the Anuk Banana in Baba Canton. The objective is to show a detailed analysis on the problems that said company raises about the social benefits. Taking into account that it was one of the first companies that started in the Pajonal Campus with banana production and marketing activities, offering various families employment close to their homes and new opportunities for improvement. The line of research in which the case study is framed is: Administrative, tax, audit, control Financial Management, it is also related to the sub-line: Companies and public and private institutions. The document is divided into three parts; the first part reflects the introduction of the company data and the case study. In the second part, he investigates and describes the problems presented in the company and in the final part, he addresses the conclusions. It shows a research methodology for the collection of information, which is the interview used with the administrator and the survey applied to employees and workers. Giving as evidence that the Anuk banana company does not confer the corresponding social benefits on its employees.